Immunomodulators in leprosy: A narrative review - Kimberly, Kesya; Ferina, Siti Aisha Nabila; Esti, Prima Kartika (Journal of General - Procedural Dermatology and Venereology Indonesia, 2024)
Background: Leprosy is a chronic infectious disease caused by Mycobacterium leprae. Current therapeutic regimen, like the multidrug therapy (MDT), are effective in treating most cases, but new cases continue to emerge in Indonesia every year. While multidrug therapy alone is adequate for treating leprosy, there is a need for adjuvant treatment options to boost the host’s immune system to prevent the worsening of leprosy and reduce the activation of M. leprae, such as immunomodulators. Discussion: Immunomodulators are drugs that can stimulate the body’s natural and adaptive defense mechanisms, acting as either immunosuppressants or immunostimulants. To understand how immunomodulatory drugs (IMiDs) work, it is important to understand the role of immunity. This article reviews the role of immunity in leprosy and discusses various immunomodulators that have been developed or investigated to enhance the host’s immune system. Substances like levamisole, thalidomide, zinc, selenium, as well as vitamins A, D, E, and C have been clinically tried in various combinations and durations, showing promise as immunomodulating agents. Conclusion: Studies have suggested that immunomodulating agents may be considered as adjuncts to MDT to enhance the elimination and clearance of bacteria, making them potential recommendations for leprosy treatment.